The Chemical Compounds of Flacourtia rukam Leaves and Their Inhibition of Angiotensin-converting Enzyme (ACE) Activity - Muharni Muharni; Heni Yohandini; Elfita Elfita; Fitrya Fitrya; Ani Sarah; Rifdah Nabila (Universitas Jenderal Soedirman, 2021)
Flacourtia rukam is a plant popular among people to treat hypertension, especially the Musi Banyuasin of south Sumatera, Indonesia. Isolation and identification of chemical compounds from F. rukam leaves and evaluation of their effects on antihypertensive activity have been conducted. Isolation of chemical compounds using chromatographic methods and identification using spectroscopic methods were compared with the reported data. The drug’s effects on antihypertension were determined using the angiotensin converting enzyme (ACE) inhibitory method. Two compounds were first reported and isolated from the leaves of F. rukam and identified as apigenin (1) and lupeol (2). These compounds were demonstrated to be effective in treating antihypertension with IC50 656.51 ± 1.55 µg/mL for apigenin and 15.12 ± 0.72 µg/mL for lupeol. It can be concluded that F. rukam leaves is a potential ACE inhibitor can be explored further as an effective antihypertensive agent.